Pembuatan prototipe Aluminium cylinder head engine dengan metode rapid prototyping dan investment casting - Masy'ari Masy'ari; Ari Dwi Prasetiyo; Edi Karyadi (Universitas Muhammadiyah Metro, 2021)
The manufacturing industry is one of the sectors that consistently continues to provide the largest national economic growth contribution to reach the target economic growth of 5.3% in 2020. In the 4.0 industry era, the manufacturing industry sector in Indonesia starts to adopt the newest digital technology like artificial intelligence, machine learning, and the internet of things, and additive manufacturing. This research aimed to develop a manufactured product in form of Aluminium cylinder head engine prototype with digital rapid prototyping and Aluminium investment casting. To reach the research goal, the research started from theoretical study and data collection. Next, the cylinder head engine is modelled in CAD (computer-aided design software and printed in 3D printer with polyvinyl butyral and polylactic acid. This 3D printed cylinder head is going to use as moulding pattern. Hereafter, the cylinder head engine is assembled with gating system and coated with a mix of cement plaster, silica sand, and kaolin soil. After the mould is dry, the mould will be burned until the 3D printed pattern is vaporized. The final step is pouring the molten Aluminium at 800°C temperature into the mould. The results showed that the casting process with a cylindrical gating system was perfectly formed, especially for the fins part. However, for the smaller fins, there were still defects in form of lumps. The mix of silica sand, gypsum cement and kaolin soil can create a strong mould. The difference in pattern material does not have a significant effect on the investment casting mould-making process.Keywords: Rapid prototyping, cylinder head engine, investment casting.